Pendidikan Multikultural Sebagai Strategi Penguatan Toleransi Dalam Masyarakat Plural di Kota Kudus - Fitri Ayu Amelia; Muhammad Miftah; Muhammad Zukhrufy Hakim Nidzami; Muhammad Arwani Ahdaf Awali; Zacky Kusuma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is focused on three main objectives, namely: 1) tracing the understanding regarding the meaning of tolerance in national and state life, 2) elaborating the essence as well as the purpose of multicultural education, and 3) evaluating the role of multicultural education in shaping tolerant character. The approach used was qualitative with literature study method. The research data was obtained from diverse literature sources, then analyzed using hermeneutic methods. The results of the study show that: 1) tolerance is a fundamental aspect to maintain the harmony of national life amidst the diversity of society. A tolerant attitude is necessary to realize peace as well as harmony in the face of differences; 2) multicultural education is very relevant for Indonesian society, especially the younger generation through formal education, given that the Indonesian nation has a complex character. This education serves to open insights so that society can accept diversity as something natural, thus enabling mutual respect and maintaining coexistence; 3) the application of multicultural education can be integrated into various subjects or lectures, such as citizenship education, Islamic religious education, and other fields. The role of educators is very important in inculcating the value of tolerance through multicultural education, by utilizing digital technologies such as the internet and online platforms combined with appropriate learning methods and media. It facilitates learners to understand the concept of tolerance as well as apply it in social, national and state life. In addition, both teachers and lecturers are expected to have comprehensive competencies, covering pedagogical, professional, personality, and social skills.